2019
DOI: 10.1186/s12906-019-2550-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth environment and organ specific variation in in-vitro cytoprotective activities of Picea mariana in PC12 cells exposed to glucose toxicity: a plant used for treatment of diabetes symptoms by the Cree of Eeyou Istchee (Quebec, Canada)

Abstract: Background The Cree of Eeyou Istchee (James Bay area of northern Quebec) suffer from a high rate of diabetes and its complications partly due to the introduction of the western lifestyle within their culture. As part of a search for alternative medicine based on traditional practice, this project evaluates the biological activity of Picea mariana (Mill.) Britton, Sterns & Poggenb. needle, bark, and cone, in preventing glucose toxicity to PC12-AC cells in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Interestingly, the PC12 cell showed high cell viability about 90% when treated with phloridzin and trilobatin at a concentration range of 0–500 μg/ml, which showed that the safety of L. litseifolius can be improved by removing impurities. Even though flavonoids (such as quercetin and kaempferol) could function to protect PC12 cells against the potential oxidative damage (Liu, Yu, Song, & Zhang, 2019), the presence of too many antioxidants can cause oxidation and thus decreasing in cell survival of L. litseifolius extracts (Downing et al, 2019). Collectively, our results suggested that it is safer to purify L. litseifolius before use.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the PC12 cell showed high cell viability about 90% when treated with phloridzin and trilobatin at a concentration range of 0–500 μg/ml, which showed that the safety of L. litseifolius can be improved by removing impurities. Even though flavonoids (such as quercetin and kaempferol) could function to protect PC12 cells against the potential oxidative damage (Liu, Yu, Song, & Zhang, 2019), the presence of too many antioxidants can cause oxidation and thus decreasing in cell survival of L. litseifolius extracts (Downing et al, 2019). Collectively, our results suggested that it is safer to purify L. litseifolius before use.…”
Section: Resultsmentioning
confidence: 99%
“…Uprety et al (2012) analyzed 49 publications related with the medicinal uses of North American Aboriginal people, including Canada's First Nations, Metis, and Inuit, and reported 546 medicinal plant taxa used by Aboriginal people of the Canadian boreal forest. The anti-diabetic properties of plants known to the Cree First Nations led to the isolation of several compounds including those with specific enzyme targets in glucose metabolism (Muhammad et al, 2012, Nistor Baldea et al, 2011, Shang et al, 2015, Downing et al, 2019. A study comparing anti-fungal activity of plants in Eastern Canada revealed a greater activity in extracts prepared from species identified by Traditional Knowledge when compared to those selected without ethnobotanical information (Jones et al, 2000).…”
Section: Asteraceae Species That Are Globally Distributed Such As Achillea Millefolium (Yarrow) Ormentioning
confidence: 99%